CASREN in Sichuan - International Livestock Research Institute (International Livestock Research Institute, 2004)
The video starts with a geographic discription of Sichuan, a town located in South East China. Sichuan is a major pig producer in China. Pig here is mostly raised in backyard crop-livestock smallholder systems with sweet potato as one of the major crops. Sweet potato is widely planted in this area and used as feed by over 75% of the household which includes pig, chicken, ducks, and cow. In many farm households, pig contributes a larger share of the family's income. In spite of the overall volume of pig produced in Sichuan, productivity per farm has been low. Pork production is 81.5 % of the total meat production in Sichuan. Farmers are short of knowledge and technology. In response to this situation, the ILRI Crop-Animal Systems Research Network (CASREN) Project team conducted participatory diagnosis of the problem on farm. This video gives a voice introduction about the CASREN project in Sichuan. Tian Le village is a representative of the subhumid subtropics. It is located in Renhe, one of the towns of Zitong County. After applying the criteria defined by the CASREN project for site selection, the team has selected Tian Le village in Zitong County as the benchmark site (BMS) where the project will operate. Tian Le village in Zitong County was selected as a benchmark site based on conditions including - farmers are very poor - sweet potato is the main forage crop - pig production plays a very important role in farmers' income. The identification of the bench mark site (BMS) was applied in combination with secondary information on household surveys and participatory rural appraisal techniques. The household survey was conducted in six villages. According to the survey, over 300 households were involved. The video also illustrates how feed is prepared and packed in plastic bags mixed with supplements and concentrates to increase the efficiency of using sweet potato and to make a balanced diet for the pigs. It also shows the variety trial fields, and presents the experimental results. The evaluation trials include high yielding varieties, root and vine yields, and chemical composition. One variety is recommended for promotion among farmers. It was found to be better than the local variety. The project team also trains farmers for sweet potato planting, crop management, storage, disease control, and variety improvement. The Sichuan Academy of Animal Sciences (SAAS) is the new partner in the CASREN Project. SAAS joined CASREN in 2002 to work on the improvement of smallholder crop-livestock systems in which sweet potato tubers and vines play an important role as feeds for pig. Memorandum of understanding between ILRI and SAAS was conducted to help enhance agricultural productivity and sustainability. The cooperation of the two institutes with the smallholders is expected to decrease poverty, hunger, and environmental degradation.